Implementation of palm biodiesel based on economic aspects, performance, emission, and wear characteristics. (15th November 2015) - Mosarof, M.H.; Kalam, M.A.; Masjuki, H.H.; Ashraful, A.M.; Rashed, M.M.; Imdadul, H.K.; Monirul, I.M.
Highlights: Global environmental protection of using alternative fuel. Economic aspects of palm oil biodiesel in Malaysia. Tribological characteristics of palm oil biodiesel in engine components. Engine performance and emission of palm oil biodiesel. Effect of temperature on density and kinematic viscosity for various biodiesel. Abstract: The high cost of energy supplies and the growing concern over the dependency on fossil fuels have impelled many countries to search for renewable and alternative energy sources. The extensive use of fossil fuels for transportation and power generation all over the world have caused the supply of fossil fuels to continuously decrease and have aggravated environmental pollution. Searching for alternative fuels has become imperative to reduce pollution and address the problems on fossil fuels. Vegetable oil fuels, such as palm oil biodiesel, serve as alternative forms of energy and are currently being studied, particularly as a diesel fuel substitute. The purpose of this study is to review the potential of palm oil as an energy source and alternative diesel fuel in terms of its performance, environmental impact, wear characteristics, and economic considerations. Compared with other vegetable oils, palm oil is a relatively sustainable, environment-friendly, less expensive, and economically beneficial potential source of energy. Palm oil plantation and production is a major industry in Malaysia, contributing to the economic growth and development of the country. The properties of palm oil biodiesel, namely, high oxidation stability, good cold properties, cetane number, and higher viscosity, makes it a suitable diesel substitute. Compared with other vegetable oils and petroleum diesel fuels, palm oil is associated with better engine performance, higher specific fuel consumption, and shorter ignition delay. Use of palm oil also reduces exhaust emission of hydrocarbon, carbon monoxide, carbon dioxide, and smoke, but not oxide of nitrogen emissions. The higher viscosity of palm oil improves its lubricating properties and anti-wear characteristics, which are favorable for various engine components. Therefore, the aim of this study is to review various studies on palm biodiesel production from different countries and compare the findings of these studies with the situation in Malaysia. This study examines the economic aspects of using palm oil, as well as its effects on performance, emission, and wear characteristics. Palm biodiesel could be the candidate with the greatest potential in all aspects.